PERLINDUNGAN HUKUM TERHADAP KEARSIPAN DI PENGADILAN NEGERI MEDAN SEBAGAI BAGIAN DARI INFORMASI PUBLIK - Sihaloho, Junico Darpindo; Nababan, Roida (Jurnal Media Informatika, 2025)
Archives are one of the important components in a court, including the Medan District Court. Based on Article 1 number 2 of the Republic of Indonesia Law Number 43 of 2009 concerning Archives, the definition of archives is "Archives are records of activities or events in various forms and media in accordance with the development of information and communication technology created and received by state institutions, local governments, educational institutions, companies, political organizations, community organizations, and individuals in carrying out community, national and state life". Archives have an important role, one of which is being part of public information in the government system, because it is a source of information that supports the implementation of administration and law enforcement in Indonesia. This study aims to determine the Implementation of Policies Prepared at the Medan District Court in protecting archives as part of Public Information and the Obstacles faced by the Medan District Court in implementing legal protection for archives. On this occasion, the author will focus on legal protection of archives at the Medan District Court as part of public information.